Infrared spectra of cool stars - nature and models (Review). - Pavlenko, Ya V. (Одеські астрономічні публікації, 2017)
Problems of modeling of IR spectra of the cool stars are discussed. Some results for M-giants, C-giants, peculiar stars and brown dwarfs are shown.